2021
DOI: 10.3390/ma14226771
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Wear Performance of AlCrN Coating on TiB2/Ti Composites at High Temperatures

Abstract: The aim of the study was to investigate effect of Ti/TiB2 composite composition and manufacturing technology parameters on the tribological behaviour of AlCrN coating-composite system. The AlCrN coating was deposited by PVD (Physical Vapour Deposition) method. The composites were manufactured by spark plasma sintering (SPS) from three variants of powders mixtures: Ti with TiB2, Ti6Al4V with TiB2 as well as Ti with B, using (five) different sintering temperatures. For each of the developed coating-composite sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…At the same time, the coating's surface layer oxidizes, forming an oxide layer that helps to reduce the friction coefficient. Previous research has shown that micro-texture can lower the temperature of the friction area, reducing coating oxidation, so that coating oxidation in TC samples is lighter and the oxide layer is easier to wear off, resulting in a periodic change in the friction coefficient [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the coating's surface layer oxidizes, forming an oxide layer that helps to reduce the friction coefficient. Previous research has shown that micro-texture can lower the temperature of the friction area, reducing coating oxidation, so that coating oxidation in TC samples is lighter and the oxide layer is easier to wear off, resulting in a periodic change in the friction coefficient [30,31].…”
Section: Discussionmentioning
confidence: 99%